2020
DOI: 10.3892/ol.2020.11948
|View full text |Cite
|
Sign up to set email alerts
|

Impact of molecular subtypes on metastatic behavior and overall survival in patients with metastatic breast cancer: A single‑center study combined with a large cohort study based on the Surveillance, Epidemiology and End Results database

Abstract: Breast cancer is a highly heterogeneous disease at the molecular level and >90% of mortalities are due to metastasis and its associated complications. The present study determined the impact of molecular subtypes on metastatic behavior and overall survival (OS) of patients with metastatic breast cancer. The influence of molecular subtypes on the sites and number of metastases in 166 patients with metastatic breast cancer from a single center were assessed; and the influence of molecular subtypes on the sites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Yann Delpech published a model without molecular subtypes classification, but our prediction model made it more comprehensive ( 23 ). We identified that HR+/HER-2− subtypes and HR+/HER2+ subtypes were more susceptible to bone metastasis, which was consistent with the rule of subtypes distribution reported by Yang ( 24 ). HR−/HER-2+ and triple-negative breast cancer more often metastasize to visceral organs, it may explain that those patients have died of visceral metastases before bone metastases were noted ( 21 , 25 ).…”
Section: Discussionsupporting
confidence: 91%
“…Yann Delpech published a model without molecular subtypes classification, but our prediction model made it more comprehensive ( 23 ). We identified that HR+/HER-2− subtypes and HR+/HER2+ subtypes were more susceptible to bone metastasis, which was consistent with the rule of subtypes distribution reported by Yang ( 24 ). HR−/HER-2+ and triple-negative breast cancer more often metastasize to visceral organs, it may explain that those patients have died of visceral metastases before bone metastases were noted ( 21 , 25 ).…”
Section: Discussionsupporting
confidence: 91%
“…Up to 70% of MBC patients experience bone involvement during their disease period [11], which is more common in hormone receptor-positive disease [12]. Bone lesions are hardly detected and monitored by CE-CT since active malignant lesions in the bones are difficult to distinguish from osteosclerotic recovering lesions [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer exhibits specific tropism for organs such as the lung, brain, liver and bone, and there are indications that this tropism is associated with breast cancer receptor status 52 . Luminal A/B tumors are the most prevalent subtype in patients with breast cancer, and they mostly metastasize to bone 53 , 54 . Luminal A/B bone metastases are typically indolent in the first years of follow-up, and patients presenting only bone metastases have higher overall survival rates than patients presenting metastasis to other distant sites 53 , 54 .…”
Section: Breast Cancer Metastasis and The Bone Nichementioning
confidence: 99%
“…Luminal A/B tumors are the most prevalent subtype in patients with breast cancer, and they mostly metastasize to bone 53 , 54 . Luminal A/B bone metastases are typically indolent in the first years of follow-up, and patients presenting only bone metastases have higher overall survival rates than patients presenting metastasis to other distant sites 53 , 54 . However, ~70% of all late-stage breast cancer patients exhibit bone metastatic foci leading to severe complications such as hypercalcemia, pain and bone fractures 52 , 55 .…”
Section: Breast Cancer Metastasis and The Bone Nichementioning
confidence: 99%